Design and Evaluation of an Integrated Mobile Web Employee Performance Management System for Hospitals: A Design Science Research Approach - Assadah Rahmawati; Suhang Zhang; Aris Munandar Arsyad (Yayasan Cendekiawan Digital Indonesia, 2026)
This study aims to address the limitations of a web-based employee performance management system in a hospital environment characterised by high work mobility and limited computer access. This study designs and evaluates an integrated mobile- and web-based employee performance management system that enables real-time work-activity reporting and improves administrative efficiency. This study uses a Design Science Research (DSR) approach to develop and validate system artefacts as a technological solution. In contrast, the system development process follows the System Development Life Cycle (SDLC), which includes planning, analysis, design, implementation, and testing stages. The proposed system integrates a mobile application with a web-based e-performance platform through an Application Programming Interface (API), thus enabling real-time data synchronisation and more flexible access. The system's main features include user authentication, a performance dashboard, recording work activities, uploading evidence of activities, and performance reporting. The results of black-box functional testing across 18 scenarios showed a 100% success rate, indicating system reliability. Usability evaluation of 32 users yielded an average score of 4.38, categorised as very good, indicating high user acceptance. The findings of this study indicate that an integrated mobile-web system can improve accessibility, support real-time performance recording, and increase administrative efficiency in hospital employee performance management. This study contributes to the development of mobile-based performance management information systems in healthcare organisations. It demonstrates the effectiveness of combining DSR and SDLC approaches to produce practical, scalable information system solutions.